Rancang Bangun Aplikasi Penilaian Kinerja Guru Menggunakan Metode Moosra Berbasis Web di SMP Negeri 1 Porsea - Ummi Seibah A.S; Muhammad Mutaqin; Muhammad Iqbal (CV. Hawari, 2025)
Teacher performance evaluation is a crucial aspect in improving the quality of education. This study aims to develop a Decision Support System (DSS) to assess teacher performance at SMP Negeri 1 Porsea using the MOOSRA (Multi-Objective Optimization on the basis of Simple Ratio Analysis) method. This method is applied due to its ability to handle multi-criteria decision-making by considering the ratio between performance scores and the weight of each criterion. The criteria used in this system include Pedagogical Competence, Professional Competence, Number of Absences, Discipline, Student Evaluation Results, and Participation in School Activities. Each criterion is assigned a weight based on its level of importance. The data were collected through observation and documentation of eight teachers with a Bachelor's degree (S1). The system produces an objective and measurable ranking of teacher performance, assisting the school in making more accurate and transparent decisions.